2020
DOI: 10.3390/ijerph17041390
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, Origins and Hazardous Effects of Polycyclic Aromatic Hydrocarbons in Topsoil Surrounding Oil Fields: A Case Study on the Loess Plateau, China

Abstract: The Loess Plateau has one of the most vulnerable ecological environments in the world, but it also contains abundant oil and gas resources that are regularly exploited, which has resulted in serious environmental problems. Therefore, it is important to analyze the polycyclic aromatic hydrocarbons (PAHs) present in the topsoil of this region. The ∑16PAHs concentrations between 1980–1999 and 2000–2019 ranged from 1134.20–15871.04 and 1010.67–18,068.80 µg kg−1, with average values of 5021.30 and 5662.82 µg kg−1. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The main factors in the spatial distribution of PAHs were land use, industrial and transportation layout, climatic conditions, and so on [34,49,56,57,68]. Chen et al [57] showed that the concentration levels of PAHs were higher in industrial areas and traffic-intensive areas than green space areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main factors in the spatial distribution of PAHs were land use, industrial and transportation layout, climatic conditions, and so on [34,49,56,57,68]. Chen et al [57] showed that the concentration levels of PAHs were higher in industrial areas and traffic-intensive areas than green space areas.…”
Section: Discussionmentioning
confidence: 99%
“…The seven PAHs in the study area were all high-molecular-weight (HMW) PAHs. The HMW PAHs were relatively more stable and prone to remain in the soil environment around the emission source, which made the model more accurate in predicting the results [49].…”
Section: Source Identification Of Pahs In Soilsmentioning
confidence: 99%
“…The toxicity and bioavailability of pollutants such as PAHs in soil are affected by soil types and soil properties (Duan et al 2016). Previous studies have found that soil particle size could affect the distribution and accumulation of pollutants in soil, and PAHs prefer to accumulate in ne soil particles (Wang et al 2020). Other factors (e.g., soil organic matter content, soil pH, soil particle size, and soil microbial activities) can also in uence the degradation of environmental contaminants such as heavy metals and PAHs in soil (Askari et al 2020;Xu et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The Loess Plateau is located in the north–central region of China, which has the largest loess coverage area in the world [ 11 ]. In recent years, due to unreasonable human behavior, such as over-farming and over-grazing, soil and water loss on the Loess Plateau has become increasingly severe, and the environment is relatively fragile [ 12 ].…”
Section: Introductionmentioning
confidence: 99%